2001
DOI: 10.1007/bf02392716
|View full text |Cite
|
Sign up to set email alerts
|

The colored Jones polynomials and the simplicial volume of a knot

Abstract: In [13], R.M. Kashaev defined a family of complex-valued link invariants indexed by integers N>~2 using the quantum dilogarithm. Later he calculated the asymptotic behavior of his invariant, and observed that for the three simplest hyperbolic knots it grows as exp(Vol(K)N/2rr) when N goes to infinity, where Vol(K) is the hyperbolic volume of the complement of a knot K [14]. This amazing result and his conjecture that the same also holds for any hyperbolic knot have been almost ignored by mathematicians since h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
415
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(424 citation statements)
references
References 24 publications
5
415
0
4
Order By: Relevance
“…It is known [14] that Kashaev's invariant is given from the colored Jones polynomial at a specific value h → 2 π i/N. By use of a result of Prop.…”
Section: Kashaev Invariant and Asymptotic Expansionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known [14] that Kashaev's invariant is given from the colored Jones polynomial at a specific value h → 2 π i/N. By use of a result of Prop.…”
Section: Kashaev Invariant and Asymptotic Expansionmentioning
confidence: 99%
“…19, Zagier further studied a "strange identity" related to the half-derivatives of the Dedekind η-function, and clarified a role of the Eichler integral with half-integral weight. From the viewpoint of the quantum invariant, Zagier's q-series was originally connected with a generating function of an upper bound of the number of linearly independent Vassiliev invariants [17], and later it was found that Zagier's q-series with q being the N-th root of unity coincides with Kashaev's invariant [5,6], which was shown [14] to coincide with a specific value of the colored Jones function, for the trefoil knot. This correspondence was further investigated for the torus knot, and it was shown [3] that Kashaev's invariant for the torus knot T (2, 2 m + 1) also has a nearly modular property; it can be regarded as a limit q being the root of unity of the Eichler integral of the Andrews-Gordon q-series, which is theta series with weight 1/2 spanning m-dimensional space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed the authors to make a non-trivial prediction about the Ooguri-Vafa partition function of the Whitehead link in the volume conjecture limit [2][3][4][5]. As rightly noted in [1], the parallel recent progress 1 in knot/link polynomial calculus in [12][13][14][15][16][17]- [44] would allow one to test this conjecture by comparison with exact formulas for the corresponding HOM-FLY polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…R. Kashaev conjectured [16] that his knot invariant K N ∈ C introduced in [15] would grow exponentially with growth rate the volume of the knot complement S 3 \ K when the integer parameter N goes to the infinity if the knot K is hyperbolic. J. Murakami and the author [34] proved that Kashaev's invariant coincides with J N K; exp(2π √ −1/N ) and generalized Kashaev's conjecture to general knots. …”
mentioning
confidence: 90%